2010
DOI: 10.1016/j.ahj.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurements of serum NT-proBNP as markers of left ventricular systolic function and remodeling in children with heart failure

Abstract: Background-Increasing serum levels of N-terminal pro-hormone brain natriuretic peptide (NTproBNP) are associated with worsening heart failure (HF) in adults. We determined whether changes in NT-proBNP level are associated with changes in symptoms and left ventricular (LV) systolic function and remodeling in children with HF secondary to dilated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 22 publications
0
33
2
8
Order By: Relevance
“…The uniform diagnostic tool for heart failure may have accounted for the similarity in findings. However, unlike other studies (11,17,18) the relationship between plasma NT-proBNP and the severity of heart failure in this study was not uniform as the subjects with moderate heart failure had a lower mean plasma NT-proBNP compared to those with mild heart failure. This may be due to the fact that infants who tend to have higher NT-proBNP values (27) contributed more to subjects with mild and severe forms of heart failure in contrast to those with moderate heart The mortality rate in this study was 3.2% which is lower than the 5.34% reported previously by Sadoh et al (30) in the same study area and 11.1% by Anah and co-workers (5).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The uniform diagnostic tool for heart failure may have accounted for the similarity in findings. However, unlike other studies (11,17,18) the relationship between plasma NT-proBNP and the severity of heart failure in this study was not uniform as the subjects with moderate heart failure had a lower mean plasma NT-proBNP compared to those with mild heart failure. This may be due to the fact that infants who tend to have higher NT-proBNP values (27) contributed more to subjects with mild and severe forms of heart failure in contrast to those with moderate heart The mortality rate in this study was 3.2% which is lower than the 5.34% reported previously by Sadoh et al (30) in the same study area and 11.1% by Anah and co-workers (5).…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, the cut-off values that have been reported have varied widely depending on the study population and the outcome parameter being evaluated. Fonseca et al (16) in a study on the identification of heart failure amongst adults reported a value of 126 pg/mL, Rusconi et al (17) in a study on children with chronic heart failure secondary to dilated cardiomyopathy reported a value of >1,000 pg/mL for the identification of moderate to severe degree of heart failure while Ekure et al (18) gave a cut off of 951 pg/mL for the identification of heart failure in a study on children with structural heart diseases in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The low discrimination power of BNP measurement on admission, as an isolated value, had also been observed by other authors, 34 who reported that serial determinations of NT-proBNP were better prognostic predictors than an isolated measurement. However, other authors have reported an adequate correlation between the measurement of BNP on the first day of life of NBIs with diaphragmatic hernia and their clinical course.…”
Section: Discussionmentioning
confidence: 70%
“…34,35 Likewise, it is necessary to study whether these outcomes are reproducible in other facilities.…”
Section: Discussionmentioning
confidence: 99%
“…La poca capacidad discriminativa del dosaje de PNB en el ingreso, como valor aislado, también fue observada por otros autores, 34 quienes reportaron que el valor de NT-pro-PNB en forma seriada era mejor predictor de pronóstico que una única muestra aislada. En cambio, otros autores reportaron buena correlación entre el dosaje de PNB el primer día de vida de niños con hernia diafragmática y su evolución.…”
Section: Discussionunclassified